Efforts of Islamic Education Teachers in Optimizing Students’ Critical Thinking Skills at SMP Negeri 1 Aikmel - Mardila, Mila; Nasri, Ulyan; Ul Haq , Muhammad Zia (Jurnal Ilmiah Profesi Pendidikan, 2025)
Critical thinking is a core 21st-century skill that must be developed through effective learning processes, particularly in Islamic Education (PAI). This study aims to describe the efforts of PAI teachers in optimizing students’ critical thinking skills at SMP Negeri 1 Aikmel. Using a qualitative approach with a case study method, data were obtained through classroom observations, interviews with PAI teachers, and documentation analysis of learning instruments. The findings show that PAI teachers employ various strategies—such as group discussions, case studies, and reflective questioning—to encourage students’ critical thinking. These efforts are supported by teachers’ readiness in designing contextual learning models, though challenged by limited instructional time and differences in student motivation. It is concluded that the structured and purposeful strategies of PAI teachers play a significant role in fostering students’ critical thinking, yet further support from educational stakeholders is still needed.